The effects of heating and tree configurations on pollutant dispersion and air temperature in Street Canyon [electronic resource] - Muhammad Noor Afiq Witri Muhammad Yazid, 1987-, author 512407; Nor Azwadi Che Sidik, 1977-, supervisor 612329; Suhaimi Mansor, supervisor 564389; Fakulti Kejuruteraan Mekanikal 8081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Thesis (Doktor Falsafah (Kejuruteraan Mekanikal))